Fortress Introduction to the Gospels, Second Edition - Powell, Mark Allan, 1953- (Book collections on Project MUSE., 2019)
With clarity and verve, Mark Allen Powell introduces the beginning student to the contents and structure of the Gospels, their distinctive characteristics, and their major themes. An introductory chapter surveys the political, religious, and social world of the Gospels, methods of approaching early Christian texts, the genre of the Gospels, and the religious character of these writings. This second edition has been updated to take fuller account of different theories regarding the Gospels, with new chapters on the historical Jesus and on gospel literature not included in our New Testament, and with a pleasing new format. Special features include illustrations and more than two dozen special topics.